Modelling of the dependencies of industrial development on marketing efficiency, innovation and technological activity indicators - Olha Ilyash; Ruslan Lupak; Taras Vasyltsiv; Olena Trofymenko; Iryna Dzhadan (Ekonomika, 2021)
This study is relevant due to the multidimensionality and interdependence of industrial development and the indicators of innovation and technological activities and marketing efficiency. The use of economic and mathematical modelling of dependencies between key macroeconomic parameters of the national economy development made it possible to qualitatively analyse the impact of the indicators of marketing efficiency, innovation and technological activities on the parameters of industrial development. The influence of the volume of financing for innovation activity, the introduction of new technological processes and the volume of production of innovative types of products on the change in the volume of sold industrial products is econometrically taken into account. The multidimensionality of the dependencies of choosing an effective model of the dependence of the volume of sold industrial products on the factors in innovation and technological activities was the reason for building a power model. The uniqueness of using an integrated model of the dependencies of innovation and technological activities and industrial development lies in taking into consideration latent factors that influence changes in industrial production, including funding for innovation in the country's industrial sector, the number of new technological processes and the level of mastering the production of new innovative types of products. The effectiveness of the study is explained by the fact that the selected system of indicators and dependencies helped to identify a number of risks to Ukraines' industrial development, for example, a critical decline in innovation and technological activities of industry.
Keywords: 330; marketing efficiency; innovation and technological activities; industrial development; modelling of the dependencies; indicators